G250(P) Supraventricular tachycardia due to blunt chesttrauma. (12th March 2018) - Haslam, J; Bird, M; Cosgrove, M; Uzun, O; Vallabhaneni, P
Abstract : Aims: Blunt cardiac injury is more prevalent in children and this may cause commotio cordis or ventricular arrhythmias. Commotio cordis is the devastating consequence of otherwise innocent-appearing chest-wall blows, with sudden cardiac death often resulting from projectiles striking the precordium. The spectrum of injuries to the heart includes damage to the great vessels, myocardial rupture or contusion, and valvular disruption. Pericardial effusions, conduction abnormalities and ventricular arrhythmias may also occur. Methods/results: We report a case of atrial arrhythmia in a 7 year old boy following blunt trauma to the chest.This previously healthy boy reported being unwell after he was hit by a football whilst playing. The impact was directly to the left anterior chest wall. A12-lead electrocardiogram (ECG) done in primary care showed supraventricular tachycardia (SVT) at a rate of 225 bpm. On arrival to the hospital his heart rate had reverted to normal limits.Twenty-four-hour Holter monitoring was normal, recording brief periods of sinus arrhythmia, infrequent sinus tachycardia of gradual onset and no episodes of SVT or ectopic activity. A transthoracic echocardiogram excluded structural abnormalities of the heart. He was started on Sotalol and is currently doing well with no sequelae from the injury. Final diagnosis of Wolf-Parkinson White syndrome was made following detailed investigations. Conclusions: We hypothesise that the blow elucidated a previously unknown congenital accessory conduction pathway. We would like to raise the awareness of such possibilities amongst children and importance of detailed investigations to detect underlying predisposing pathologies.